EKSPLORASI ETNOMATEMATIKA PADA KERAPAN SAPEH BRUJUL - Nur Fadhilah; Nur Wiji Sholikin (PT Innovative Academic Journals, 2025)
Ethnomathematics is the study of the relationship between mathematics and culture in everyday life. One cultural tradition that has mathematical elements is Kerapan Sapeh Brujul, which is a cow racing competition held in a muddy area in Probolinggo City, East Java. This research aims to identify and analyze the mathematical concepts contained in Kerapan Sapeh Brujul, including the geometry of the race track, symmetry patterns in cow decorations, as well as calculating speed and load balance on the cow cart frame. This research uses a descriptive qualitative approach using observation, interviews and literature study methods. The results of the research show that in Kerapan Sapeh Brujul there are geometric concepts in the design of race tracks and train frames or keleles, patterns and symmetry in the design of cow ornaments, as well as calculations of speed and acceleration in determining race winners. Apart from that, the concept of balance and load distribution on the carriage frame or keleles also influences the stability of the cow when running. The results of this research show that Kerapan Sapeh Brujul is not just a cultural tradition, but also has academic value that can be integrated into culture-based mathematics learning. It is hoped that this research can be a reference for educators in developing learning methods that are more contextual and interesting for students.